Invisible Island by Ron Roy; illustrated by John Steven Gurney - Roy, Ron; Gurney, John, ill (New York Random House, 1999)
While picnicking on Squaw Island Dink, Josh and Ruth Rose find a hundred-dollar bill and when they return to explore further they find an entire cave full of money.
A Stepping Stone book.
Keywords: Islands-Fiction; Counterfeits and counterfeiting-Fiction; Mystery and detective stories